Lethal and Inhibitory Effects of Sodium Chloride on Thermally Stressed Staphylococcus aureus - Erwin, Daniel G. (1973)
Iandolo and Ordal used a double-medium technique for the study of thermal injury in Staphylococcus aureus. In their system sodium chloride (salt) was used to distinguish the salt-sensitive from the salt-insensitive portions of the viable population remaining after thermal stressing. The data reported here show that nutrient medium containing salt was lethal for cells immediately postinjury and that nutrient medium containing salt was only inhibitory to injured cells if those cells had been incubated for 30 min in nutrient medium, buffered salt, or buffer alone prior to subjection to nutrient medium containing salt. Sodium ion was implicated as the active agent since nutrient media containing potassium chloride or glycerol (osmotic equivalence) produced neither inhibition nor the lethal effect. The inhibitory effect was interpreted as defining an early stage in the thermal injury recovery process.